2019
DOI: 10.25260/ea.19.29.3.0.860
|View full text |Cite
|
Sign up to set email alerts
|

Estado del conocimiento en ecología y conservación de los roquedales de la Argentina: Una revisión

Abstract: RESUMEN.Los roquedales proveen recursos que aprovechan diferentes especies, lo cual los convierte en sitios relevantes para conservar la biodiversidad. Sin embargo, estos sistemas permanecen poco estudiados a nivel global, y la Argentina no es la excepción. Por este motivo, realizamos una revisión bibliográfica para aportar información sobre el estado del conocimiento en relación con el rol ecológico de los roquedales y sobre su importancia como elementos clave de diferentes ecosistemas argentinos. Encontramos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 64 publications
0
3
0
2
Order By: Relevance
“…However, the limited survey coverage emphasizes the necessity for extensive exploration of Isla de los Estados to fully account for the distribution of breeding sites. The ecological relevance of rock outcrops is proposed in this study as potential landmarks for orientation, remarking another function as the ones suggested by GomezCarella et al (2019). Nevertheless, an interesting contrast arises when considering New Zealand's predator-free islands, where burrow density was highest in grasslands(Charleton 2009), revealing the complexity of habitat preferences among different populations of sooty shearwaters.Globally, the sooty shearwater population is estimated at 4.4 million pairs, or approximately 19.0-23.6 million individuals(Newman et al 2009, Waugh et al 2013).…”
mentioning
confidence: 53%
“…However, the limited survey coverage emphasizes the necessity for extensive exploration of Isla de los Estados to fully account for the distribution of breeding sites. The ecological relevance of rock outcrops is proposed in this study as potential landmarks for orientation, remarking another function as the ones suggested by GomezCarella et al (2019). Nevertheless, an interesting contrast arises when considering New Zealand's predator-free islands, where burrow density was highest in grasslands(Charleton 2009), revealing the complexity of habitat preferences among different populations of sooty shearwaters.Globally, the sooty shearwater population is estimated at 4.4 million pairs, or approximately 19.0-23.6 million individuals(Newman et al 2009, Waugh et al 2013).…”
mentioning
confidence: 53%
“…En los suelos rocosos y poco desarrollados solo pueden habitar plantas que estén adaptadas a este ambiente, debido al estrés hídrico, alta exposición a los rayos solares y al escaso desarrollo de sus raíces (Cantero et al, 2021). Las especies del género Grindelia y los líquenes están adaptados a este tipo de suelos (Chen et al, 2000;Gómez Carella et al, 2019). En el matorral de Colliguaja integerrima, los menores valores de diversidad y equitatividad podrían deberse a la dominancia de este arbusto sobre toda la vegetación.…”
Section: Discussionunclassified
“…Se utilizaron los buscadores: Scopus y Scholar Google. Las palabras clave (en español e inglés) fueron "neo-ecosistemas, dryland salinity, salinización del suelo, anegamiento por salinidad y humedales" considerando el período 1990-2021(Gómez Carella et al 2019. Del resultado de esta búsqueda se seleccionaron 3534 artículos que contenían los términos relacionados con la temática.…”
Section: Caracterización De Neo-humedales Medianteunclassified